2021
DOI: 10.3390/biomedicines9111573
|View full text |Cite
|
Sign up to set email alerts
|

The Isoform GC1f of the Vitamin D Binding Protein Is Associated with Bronchiectasis Severity

Abstract: Vitamin D modulates immune responses and its deficiency has been observed in more than 60% of bronchiectasis patients. Vitamin D binding protein (DBP) is coded by the GC gene, is involved in the transport of vitamin D, and includes a number of isoforms based on single nucleotide polymorphisms (SNPs) in the coding region at rs7041 and rs4855. We evaluated the possible clinical impact of DBP polymorphisms and isoforms in an observational, cross-sectional study conducted in 116 bronchiectasis patients, who were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Supporting this finding are results showing that the GC1f genotype is associated with an augmented risk of chronic inflammatory diseases. Thus, (1) in chronic obstructive pulmonary disease (COPD), GCf1 was strongly associated with the risk of disease [ 55 ]; (2) in bronchiectasis, patients carrying the GC1f isoform have a more severe disease and more chronic infections in comparison with those without the GC1f isoform [ 56 ]; (3) in inflammatory bowel disease the GC2 isoform was less frequently observed in patients compared with healthy controls, suggesting a protective role [ 57 ]. On the other hand, the same GC2 isoform was associated with asthma susceptibility in the Chinese Han population [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this finding are results showing that the GC1f genotype is associated with an augmented risk of chronic inflammatory diseases. Thus, (1) in chronic obstructive pulmonary disease (COPD), GCf1 was strongly associated with the risk of disease [ 55 ]; (2) in bronchiectasis, patients carrying the GC1f isoform have a more severe disease and more chronic infections in comparison with those without the GC1f isoform [ 56 ]; (3) in inflammatory bowel disease the GC2 isoform was less frequently observed in patients compared with healthy controls, suggesting a protective role [ 57 ]. On the other hand, the same GC2 isoform was associated with asthma susceptibility in the Chinese Han population [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…RV has been shown to inhibit the profibrotic action of TGF-b1 in patients with pulmonary fibrosis [6,8]. Oriano et al [9] confirmed that VD-binding protein (DBP) polymorphisms and the resulting isoform are involved in the pathogenesis and severity of bronchiectasis, where DBP is coded by the GC gene. Notably, the GC1f isoform (rs7041/rs4588 A/G) correlated with a more severe disease, a higher incidence of chronic infections and a lower bronchiectasis etiology and comorbidity index (BACI) score.…”
mentioning
confidence: 98%